Glass, method of preparation and use
By adjusting the glass component ratio and chemical strengthening treatment, high-strength, scratch-resistant glass was prepared, solving the problem of insufficient performance of existing soda-lime-silicon glass at low thicknesses. It is suitable for applications such as smart terminal displays and automotive protective glass.
Patent Information
- Application Number
- CN202510114833.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-01-24
AI Technical Summary
Existing soda-lime silica glass cannot simultaneously meet the requirements of high strength, high deformation resistance and scratch resistance at low thickness, making it difficult to meet the needs of applications such as smart terminal displays and automotive protective glass.
By adjusting the proportions of glass components, including the weight relationships of silicon dioxide, aluminum oxide, and boron oxide, and combining this with chemical strengthening treatment, a glass with high strength and scratch resistance at a low thickness is prepared.
It achieves improved strength, hardness, and scratch resistance of glass at low thickness, making it suitable for applications such as smart terminal displays and automotive protective glass.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass manufacturing technology, and in particular to a type of glass, a preparation method thereof, and its applications. Background Technology
[0002] With the trend towards lighter and thinner designs in smartphones, tablets, and other smart devices, the thickness of display components in these devices is constantly decreasing. However, the main material of display components is glass, and as the thickness decreases, the strength of the glass also decreases. Furthermore, the requirements for the scratch resistance of display components are becoming increasingly stringent. Existing soda-lime silica glass cannot simultaneously meet the requirements of high strength, high deformation resistance, and scratch resistance at low thicknesses. Therefore, it is necessary to develop a type of glass that still possesses high strength, high hardness, and good scratch resistance at low thicknesses. Summary of the Invention
[0003] The main objective of this invention is to develop a glass, a preparation method, and an application that achieves sufficient strength and hardness at a relatively low thickness to meet usage requirements. This will satisfy the hardness and strength requirements of glass in various application scenarios, such as smart terminal displays, automotive protective glass, and windows.
[0004] To achieve the above objectives, the present invention provides a glass comprising, by weight percentage: silicon dioxide: 61wt%–66wt%; aluminum oxide: 11wt%–18wt%; boron oxide: 1wt%–5wt%; sodium oxide: 10wt%–15wt%; potassium oxide: 0.4wt%–5wt%; magnesium oxide: 0.5wt%–5wt%; calcium oxide: 0.1wt%–2wt%; wherein the weight relationship of silicon dioxide, aluminum oxide, and boron oxide is as follows: The weight percentage of silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide, and calcium oxide satisfies the following: 30.01 ≤ 0.36 × SiO2 + 0.78 × Al2O3 - 0.53 × B2O3 ≤ 35.15; and / or the weight percentage of silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide, and calcium oxide satisfies the following: 12.28 ≤ 0.42 × SiO2 - 0.47 × (B2O3 - Al2O3) - 1.03 × (Na2O - K2O) - 2.58 × (MgO - CaO) ≤ 22.91.
[0005] In one embodiment, the glass comprises, by weight percentage, the following components: silicon dioxide: 61.9 wt% to 65.2 wt%; aluminum oxide: 12.3 wt% to 17.3 wt%; boron oxide: 1.6 wt% to 4.3 wt%; sodium oxide: 10.8 wt% to 14.2 wt%; potassium oxide: 1 wt% to 4.2 wt%; magnesium oxide: 1.1 wt% to 4.2 wt%; calcium oxide: 0.3 wt% to 1.6 wt%; wherein the weight percentages of silicon dioxide, aluminum oxide, and boron oxide are... The weight relationships, expressed as a percentage by weight, satisfy the following: 31.03 ≤ 0.36 × SiO2 + 0.78 × Al2O3 - 0.53 × B2O3 ≤ 34.69; and / or, the weight relationships of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide, and calcium oxide, expressed as a percentage by weight, satisfy the following: 14.02 ≤ 0.42 × SiO2 - 0.47 × (B2O3 - Al2O3) - 1.03 × (Na2O - K2O) - 2.58 × (MgO - CaO) ≤ 21.34.
[0006] In one embodiment, the T of the glass 200 T 35000 T x and T S The following relationship must be satisfied: 2.66 ≤ (T) 200 -T 35000 ) / (T x -T S )≤2.95; where T 200 The temperature at which the viscosity of glass is 200 poise, T 35000 The temperature at which the viscosity of glass reaches 35,000 poise, T x The upper limit temperature for glass crystallization, T S This is the glass softening temperature.
[0007] In one embodiment, the T of the glass 200 ≤1600℃.
[0008] In one embodiment, the T of the glass 35000 ≤1089℃.
[0009] In one embodiment, the T of the glass x ≤1000℃.
[0010] In one embodiment, the T of the glass S ≤827℃.
[0011] In one embodiment, the T of the glass 35000 and the T of the glass x The difference is greater than 80℃.
[0012] In one embodiment, when the thickness of the glass is 0.6 mm, the stress intensity CS value of the glass is >900 MPa.
[0013] In one embodiment, when the thickness of the glass is 0.6 mm, the stress layer depth (DOL) value of the glass is ≥41 μm.
[0014] In one embodiment, when the thickness of the glass is 0.6 mm, the Vickers hardness value of the glass is >700 HV.
[0015] The present invention also proposes a method for preparing the glass, characterized in that the method for preparing the glass includes the following steps: S10. Mix, melt, clarify, homogenize, shape, and anneal the components in the raw materials according to the proportions to obtain intermediate glass products; S20. Cut the glass intermediate obtained in step S10. S30. The glass intermediate product after cutting in step S20 is chemically strengthened to obtain the glass.
[0016] In one embodiment, in step S20, the thickness of the glass intermediate after cutting is controlled to be 0.02mm~0.6mm.
[0017] In one embodiment, step S30, the chemical strengthening specifically includes the following steps: The glass intermediates after cutting in step S20 are kept at 270℃~320℃ for 25min~40min, and then placed in molten salt for chemical strengthening treatment. The chemical strengthening temperature is controlled at 400℃~430℃, and the chemical strengthening time is controlled at 0.25h~4h. The molten salt includes 0~1wt% NaNO3 and 99wt%~100wt% KNO3.
[0018] The present invention also proposes a display device that utilizes the glass.
[0019] The technical solution of this invention provides a composition and specific ratio of aluminosilicate glass, which, based on silicon dioxide, aluminum oxide, and boron oxide as the main components, adds sodium oxide, potassium oxide, magnesium oxide, and calcium oxide to strengthen the network structure in the glass phase. This invention also achieves this by rationally controlling the composition and specific ratio of the aluminosilicate glass, allowing the glass to reach a specific viscosity at a temperature T. 200 and T 35000 And the upper limit temperature T of glass crystallization. x Glass softening temperature T SBy satisfying specific relationships, the strength, hardness, and scratch resistance of the glass are further improved, while the difficulty of glass forming during the glass production process is reduced. In the preparation method of this invention, the pretreatment and chemical strengthening process promotes rapid ion exchange on the glass surface and reaches a certain stress layer depth, thereby further enhancing the stress intensity and stress depth of the glass, thus enhancing the scratch resistance and impact resistance of the glass. Detailed Implementation
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.
[0022] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution where both A and B are satisfied simultaneously. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.
[0023] The technical problem addressed by this application is that, with the increasing popularity of smart terminals such as mobile phones and tablets and their trend towards thinner and lighter designs, the thickness of display components such as screens on these smart devices is required to be continuously reduced. However, the strength of glass decreases significantly with the reduction in thickness, making it brittle. Existing soda-lime silicon glass cannot simultaneously meet the requirements of low thickness, high strength, high deformation resistance, and scratch resistance.
[0024] To address the aforementioned technical problems, this invention proposes a glass with strength and hardness at low thickness that can meet the requirements of glass materials for smart terminal displays, automotive protective glass, and automotive windows. The invention also proposes a glass, a preparation method, and an application.
[0025] This invention provides a glass comprising, by weight percentage: silicon dioxide: 61wt%–66wt%; aluminum oxide: 11wt%–18wt%; boron oxide: 1wt%–5wt%; sodium oxide: 10wt%–15wt%; potassium oxide: 0.4wt%–5wt%; magnesium oxide: 0.5wt%–5wt%; calcium oxide: 0.1wt%–2wt%; wherein the weight relationship of silicon dioxide, aluminum oxide, and boron oxide is as follows: The weight ratio of silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide, and calcium oxide, calculated as a percentage by weight, satisfies the following: 30.01 ≤ 0.36 × SiO2 + 0.78 × Al2O3 - 0.53 × B2O3 ≤ 35.15; and / or, the weight relationship of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide, and calcium oxide, calculated as a percentage by weight, satisfies the following: 12.28 ≤ 0.42 × SiO2 - 0.47 × (B2O3 - Al2O3) - 1.03 × (Na2O - K2O) - 2.58 × (MgO - CaO) ≤ 22.91.
[0026] It should be noted that the silica content in the glass is 61-66 wt%, specifically 61 wt%, 61.9 wt%, 62.6 wt%, 63.3 wt%, 64.1 wt%, 65.2 wt%, and 66 wt%, including but not limited to the values listed above. As the main component of the glass's mesh structure, silica plays a crucial role in the technical solution of this invention. When the silica content is below 61 wt%, the glass becomes difficult to form during the glass-forming process, and the resulting glass exhibits an increased coefficient of thermal expansion, reduced chemical corrosion resistance, and poor stability. Conversely, when the silica content is above 66 wt%, the glass's melting point increases, increasing the difficulty of melting during production. Furthermore, excessively high silica content reduces the glass's impact resistance, making it unsuitable for producing thinner glass.
[0027] It should also be noted that the alumina content in the glass is 11wt% to 18wt%, which can be 11wt%, 12.3wt%, 13.5wt%, 14.4wt%, 16.4wt%, 17.3wt%, or 18wt%, including but not limited to the values listed above. As a network modifier, the aluminum-oxygen tetrahedra [AlO4] formed by Al in alumina and non-bridging oxygen can be linked to silicon-oxygen tetrahedra [SiO4]. This allows the previously unconnected silicon-oxygen tetrahedra [SiO4] in the glass to be connected through the aluminum-oxygen tetrahedra, increasing the connectivity within the glass network and making the structure more compact, thereby improving the mechanical strength and thermal stability of the glass. The aluminum-oxygen tetrahedra are larger in volume than silicon-oxygen tetrahedra, resulting in a glass network structure with larger gaps, which facilitates ion exchange and improves the glass's scratch resistance and drop resistance. It should also be noted that excessive alumina can form an aluminum-oxygen octahedron [AlO6] structure. The aluminum-oxygen octahedrons are free between the network structures and do not participate in cross-linking. Excessive aluminum-oxygen octahedron content will destroy the original silicon-oxygen network structure, reduce the stability of the glass structure, and affect its impact resistance. When the alumina content is insufficient, the glass is more susceptible to hydrolysis or acid and alkali corrosion, and the strength and impact resistance of the glass will also be significantly reduced.
[0028] It should also be noted that the boron oxide content in the glass is 1wt% to 5wt%; it can be 1wt%, 1.6wt%, 2.5wt%, 3wt%, 3.8wt%, 4.3wt%, 5wt%, or more, including but not limited to the values listed above. When the boron oxide content is low, it mainly exists in the glass in the form of a four-coordinate structure. As the content increases, the three-coordinate structure gradually increases. The four-coordinate structure usually exists in a tetrahedral form, connecting with other units in the glass network through shared oxygen atoms, forming a more compact network structure; the three-coordinate structure usually exists in a planar triangular form, forming a looser network structure. A higher proportion of four-coordinate structures is beneficial to enhancing the strength and hardness of the glass, while a higher proportion of three-coordinate structures allows the glass to better adapt to volume changes during cooling and reduces potential cracks, which is beneficial to lowering the melting point and increasing the toughness of the glass. By controlling the proportion of boron oxide and other components, the four-coordinate and three-coordinate structures of boron oxide in the glass are kept in balance, enabling the glass of the present invention to have both high strength and scratch resistance under relatively thin conditions.
[0029] It should also be noted that the sodium oxide content in the glass is 10wt% to 15wt%; it can be 10wt%, 10.8wt%, 11.6wt%, 12.7wt%, 13.2wt%, 14.2wt%, or 15wt%, including but not limited to the values listed above. Sodium oxide, as a network exogenous substance, is one of the main exchange ions in the chemical strengthening process, acting as a flux. On the one hand, it can lower the melting temperature of the glass; on the other hand, it can improve the chemical stability of the glass.
[0030] It should also be noted that the potassium oxide content in the glass ranges from 0.4 wt% to 5 wt%; it can be 0.4 wt%, 1 wt%, 1.6 wt%, 2.8 wt%, 3.7 wt%, 4.2 wt%, or 5 wt%, including but not limited to the values listed above. Potassium oxide can also adjust the high-temperature viscosity of the glass during melting and its mechanical strength after forming. However, unlike sodium oxide, potassium oxide does not participate in the ion exchange process. Therefore, in the subsequent strengthening process, the main component of the molten salt is potassium oxide. Excessive potassium oxide will inhibit ion exchange in the glass, which is detrimental to improving the strength of the glass.
[0031] It should also be noted that the magnesium oxide content in the glass ranges from 0.5 wt% to 5 wt%; it can be 0.5 wt%, 1.1 wt%, 2 wt%, 2.8 wt%, 3.3 wt%, 4.2 wt%, or 5 wt%, including but not limited to the values listed above. Magnesium oxide is mainly used to promote glass melting. Magnesium oxide can also generate a potential difference to promote ion exchange, thereby improving the stress strength and depth of the glass. If the magnesium oxide content is less than 0.5 wt%, it cannot significantly improve the glass melting effect; if the content is higher than 5 wt%, it will lead to an increase in the viscosity of the molten glass, promote crystallization, and reduce the transparency and toughness of the glass.
[0032] It should also be noted that the calcium oxide content in the glass is 0.1wt% to 2wt%; it can be 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 1.2wt%, 1.6wt%, 2wt%, or more, including but not limited to the values listed above. Calcium oxide can reduce the crystallization tendency of molten glass and regulate the rate and depth of ion exchange, thereby improving the chemical stability and mechanical strength of the glass.
[0033] It should also be noted that the weight relationship of silicon dioxide, aluminum oxide, and boron oxide, expressed as a percentage by weight, satisfies: 30.01 ≤ 0.36 × SiO2 + 0.78 × Al2O3 - 0.53 × B2O3 ≤ 35.15. In this invention, silicon dioxide, aluminum oxide, and boron oxide are mainly connected in a three-dimensional tetrahedral structure in the glass network structure. By limiting the above quantitative relationship, the proportions of silicon-oxygen tetrahedra, aluminum-oxygen tetrahedra, and boron-oxygen tetrahedra constituting the main body of the grid in the glass structure can reach a special balance, thereby improving the connection degree of the glass network structure and obtaining a stable glass network structure. Silicon dioxide is the main glass network structure, aluminum oxide preferentially oxidizes boron into the glass network structure, and aluminum-oxygen tetrahedra can effectively shield easily polarized oxygen atoms, making it difficult for them to move and inhibiting the precipitation of cristobalite.
[0034] It should also be noted that the weight relationships of silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide, and calcium oxide, expressed as weight percentages, satisfy the following: 12.28 ≤ 0.42 × SiO2 - 0.47 × (B2O3 - Al2O3) - 1.03 × (Na2O - K2O) - 2.58 × (MgO - CaO) ≤ 22.91. By ensuring that the components in the glass satisfy the above relationship, the glass exhibits higher chemical stability and better crystallization performance, and also possesses better chemical strengthening properties.
[0035] In one embodiment, the glass comprises, by weight percentage, the following components: silicon dioxide: 61.9 wt%–65.2 wt%; aluminum oxide: 12.3 wt%–17.3 wt%; boron oxide: 1.6 wt%–4.3 wt%; sodium oxide: 10.8 wt%–14.2 wt%; potassium oxide: 1 wt%–4.2 wt%; magnesium oxide: 1.1 wt%–4.2 wt%; calcium oxide: 0.3 wt%–1.6 wt%; wherein the weight percentages of silicon dioxide, aluminum oxide, and boron oxide are specified. The weight percentage of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide satisfies the following condition: 31.03≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤34.69; and / or, the weight percentage of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide satisfies the following condition: 14.02≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤21.34.
[0036] It should be noted that, through multiple experiments during the research and development process, the inventors discovered that when the content of each component in the glass changes, the CS value and Vickers hardness value of the glass produced under the condition of unchanged preparation process show the same trend at low thickness, while the trend of the DOL value of the glass is opposite to the former. The inventors also found that when the content of each component in the glass is further limited to meet the above-mentioned ratio and weight relationship, the glass produced has better overall performance at low thickness, and at the same time has higher strength, hardness and scratch resistance.
[0037] In one embodiment, the T of the glass 200 T 35000 T x and T S The following relationship must be satisfied: 2.66 ≤ (T) 200 -T 35000 ) / (T x -T S )≤2.95; where T 200 The temperature at which the viscosity of glass is 200 poise, T 35000 The temperature at which the viscosity of glass reaches 35,000 poise, T x The upper limit temperature for glass crystallization, T S This is the glass softening temperature.
[0038] It should be noted that in this embodiment, M is set as the glass crystallization stabilization factor, M = (T 200 -T 35000 ) / (T x -T S The glass crystallization stability factor (M) is typically used to assess a glass's resistance to crystallization. Setting a reasonable M value can effectively prevent unnecessary crystallization during high-temperature processing, forming, and long-term use, thus facilitating the optimization of production process parameters. Generally, a larger M value results in easier glass manufacturing; a smaller M value results in greater manufacturing difficulty. In this embodiment, the value of M is limited to a certain range, ensuring that the resulting glass exhibits higher hardness, strength, and scratch resistance even at low thicknesses.
[0039] It should also be noted that the T in the glass of this application 200 and T 35000 The determination methods include: using a rotational high-temperature viscometer to determine the high-temperature viscosity-temperature curve of glass according to standard ASTM C-965, and the temperature T corresponding to a viscosity of 200P. 200 Temperature T corresponding to a viscosity of 35000P 35000 .
[0040] It should also be noted that the T in the glass of this application xThe determination methods include: using the gradient furnace method to determine the upper limit temperature for glass crystallization, in accordance with standard ASTM C-829.
[0041] It should also be noted that the T in the glass of this application s The determination methods include: determining the softening point of glass according to the standard ASTM C338.
[0042] In one embodiment, the T of the glass 200 ≤1600℃.
[0043] In one embodiment, the T of the glass 35000 ≤1089℃.
[0044] In one embodiment, the T of the glass x ≤1000℃.
[0045] In one embodiment, the T of the glass S ≤827℃.
[0046] It should be noted that, by separately measuring the T of the glass... 200 T 35000 T x and T S By imposing limits, on the one hand, the temperature corresponding to different process nodes in the glass production process is lower, which helps to save energy and production costs; on the other hand, it can ensure that the glass produced has higher hardness, strength and scratch resistance at a lower thickness.
[0047] In one embodiment, the T of the glass 35000 and the T of the glass x The difference is greater than 80℃.
[0048] It should be noted that △T=T is set. 35000 -T x △T is usually used to represent the safe temperature range for glass to avoid crystallization during forming or processing. It can also be understood as the processing window of glass. The larger the △T, the wider the temperature range in which the glass can remain amorphous, thereby reducing the risk of defects caused by premature crystallization.
[0049] In one embodiment, when the thickness of the glass is 0.6 mm, the stress intensity CS value of the glass is >900 MPa.
[0050] In one embodiment, when the thickness of the glass is 0.6 mm, the stress layer depth (DOL) value of the glass is ≥41 μm.
[0051] In one embodiment, when the thickness of the glass is 0.6 mm, the Vickers hardness value of the glass is >700 HV.
[0052] The present invention also provides a method for preparing the glass, comprising the following steps: S10. Mix, melt, clarify, homogenize, shape, and anneal the components in the raw materials according to the proportions to obtain intermediate glass products; S20. Cut the glass intermediate obtained in step S10. S30. The glass intermediate product after cutting in step S20 is chemically strengthened to obtain the glass.
[0053] In one embodiment, in step S20, the thickness of the glass intermediate after cutting is controlled to be 0.02mm~0.6mm.
[0054] In one embodiment, step S30, the chemical strengthening specifically includes the following steps: The glass intermediates after cutting in step S20 are kept at 270℃~320℃ for 25min~40min, and then placed in molten salt for chemical strengthening treatment. The chemical strengthening temperature is controlled at 400℃~430℃, and the chemical strengthening time is controlled at 0.25h~4h. The molten salt includes 0~1wt% NaNO3 and 99wt%~100wt% KNO3.
[0055] It should be noted that the heat insulation treatment before chemical strengthening makes the temperature distribution of the glass more uniform, avoiding stress concentration caused by local temperature differences; it also makes it easier for sodium ions on the glass surface to be displaced, thereby increasing the depth and efficiency of ion exchange. This helps to increase the thickness of the compressive stress layer on the glass surface, enhancing its impact resistance.
[0056] In one specific embodiment, the method for preparing the glass includes the following steps: S10. Calculate the required raw materials according to the designed glass composition, mix them evenly, and pour them into a platinum-rhodium crucible. Simultaneously, add a clarifying agent, sodium chloride, at 0.5 wt% of the raw materials. Heat at 1600℃~1640℃ for 7 hours and mix evenly. Remove the crucible and pour the molten glass into a preheated mold to form a block. Place the formed glass block in a muffle furnace and hold at 600℃ for 2 hours. Cool to room temperature and remove. S20. Cut the intermediate glass product obtained in step S10; control the thickness of the cut intermediate glass product to be 0.02~0.6mm. S30. The glass intermediate product cut in step S20 is kept at 270~320℃ for 25~40 minutes. Then, the glass intermediate product after heat preservation is placed in molten salt for chemical strengthening treatment. The chemical strengthening temperature is controlled at 400~430℃ and the chemical strengthening time is controlled at 0.25~4h. The molten salt includes 0~1wt% NaNO3 and 99~100wt% KNO3.
[0057] It should be noted that the above description of the preparation method is only used to explain the content of the present invention and does not limit the scope of protection of the present invention.
[0058] Furthermore, the present invention also proposes a display device that utilizes the aforementioned glass. After applying the glass, the display device exhibits better drop resistance, impact resistance, and scratch resistance.
[0059] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.
[0060] Unless otherwise specified, all raw materials used in the embodiments and comparative examples of this application are commercially available, and the methods used are conventional methods in the art.
[0061] Relevant testing methods: (1) T was determined according to the method of standard ASTM-C338. s Value; T was determined according to standard ASTM C-965. 200 and T 35000 T was determined according to standard ASTM C-829. x ; (2) The surface stress intensity CS value and surface stress depth DOL value of the glass were determined using the Orihara FSM-6000LE surface stress meter from Japan; (3) The Vickers hardness value of the glass was determined with reference to standard GB / T4340.4-2022.
[0062] Examples 1-7 Examples 1-7 are glasses prepared with different raw material ratios, the difference being the different amounts of each component, as shown in Table 1 (unit: wt%).
[0063] Comparative Example 1 Comparative Example 1 is based on Example 1, except that the amount (weight percentage) of each component is different, as shown in Table 1 (unit: wt%).
[0064] Table 1
[0065] As shown in Table 1, the mass percentage of silicon dioxide in Comparative Example 1 is 67%, which does not meet the component requirements of this invention.
[0066] The preparation process of Examples 1-7 and Comparative Example 1 is the same, specifically including the following steps: S10. Calculate the required raw materials according to the designed glass composition, mix them evenly, and pour them into a platinum-rhodium crucible. Simultaneously, add a clarifying agent, sodium chloride, at 0.5 wt% of the raw materials. Heat at 1600℃~1640℃ for 7 hours and mix evenly. Remove the crucible and pour the molten glass into a preheated mold to form a block. Place the formed glass block in a muffle furnace and hold at 600℃ for 2 hours. Cool to room temperature and remove. S20. Cut the intermediate glass product obtained in step S10; control the thickness of the cut intermediate glass product to be 0.02~0.6mm. S30. The glass intermediate product cut in step S20 is placed at 300°C for 30 minutes. Then, the glass intermediate product after heat preservation is placed in molten salt for chemical strengthening treatment. The chemical strengthening temperature is controlled at 400°C and the chemical strengthening time is controlled at 4 hours. The molten salt includes 1 wt% NaNO3 and 99 wt% KNO3.
[0067] The specific parameters of the preparation process in Examples 1-7 and Comparative Example 1 are shown in Table 2.
[0068] Let A = 0.36 × SiO2 + 0.78 × Al2O3 - 0.53 × B2O3; Set B = 0.42 × SiO2 - 0.47 × (B2O3 - Al2O3) - 1.03 × (Na2O - K2O) - 2.58 × (MgO - CaO); It should be noted that "SiO2", "Al2O3", "B2O3", "Na2O", "K2O", "MgO" and "CaO" in the above formula refer to the weight percentage of the corresponding components in each embodiment or comparative example.
[0069] Table 2
[0070] The properties of the glasses prepared in Examples 1-7 and Comparative Example 1 were measured, and the details are shown in Table 3.
[0071] Table 3
[0072] Analysis of Tables 2 and 3 shows that the glass prepared according to the formula in this invention, i.e., the glass prepared in Examples 1-7, has a melting temperature T.200 ≤1600℃; Molding temperature T 35000 ≤1089℃; softening point T S ≤827℃, upper limit temperature for crystallization T x ≤1000℃, △T=(T 35000 -T x The glass temperature is >80℃, and the glass stability factor is 2.66≤M≤2.95. The strengthening temperature is 400℃~430℃, and the strengthening time is 0.25 hours~4 hours. When the thickness of the glass is 6mm, the corresponding CS value is >900MPa, DOL value is >41μm, and Vickers hardness value is >700HV.
[0073] In Comparative Example 1, the weight percentage of silicon dioxide was 67% and the value of A was 36.59, which does not meet the requirements of this invention. 200 =1611℃, T 35000 =1080℃, T S =797℃, T x =1018℃, ΔT=(T 35000 -T x At 62℃, the glass crystallization stability factor M = 2.40, making the glass difficult to produce and shape.
[0074] Examples 8-11 Examples 8-11 are based on Example 1, with the difference that the glass thickness is different in step S20 and the chemical strengthening time is different in step S30, as detailed in Table 4.
[0075] Table 4
[0076] Analysis of Table 4 shows that the glass prepared in Examples 8-11, with a thickness of only 0.02 mm, can simultaneously meet the requirements of a CS value of 420 MPa, a DOL value of 12 μm, and a Vickers hardness value of 600 HV.
[0077] The above description is merely an exemplary embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A type of glass, characterized in that, The glass comprises the following components by weight percentage: Silicon dioxide: 61.9 wt%~65.2 wt%; Alumina: 12.3wt%~17.3wt%; Boron oxide: 1.6wt%~4.3wt%; Sodium oxide: 10.8 wt%–14.2 wt%; Potassium oxide: 1 wt%–4.2 wt%; Magnesium oxide: 1.1 wt%–4.2 wt%; Calcium oxide: 0.3wt%~1.6wt%; The weight relationship of silicon dioxide, aluminum oxide, and boron oxide, expressed as a weight percentage, satisfies the following: 31.03≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤34.69; And / or, the weight relationships of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide, and calcium oxide, expressed as weight percentages, satisfy the following: 14.02≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤21.34; The glass's T 200 T 35000 T x and T S The following relationship must be satisfied: 2.66≤(T 200 -T 35000 ) / (T x -T S )≤2.95; In the formula, T 200 The temperature at which the viscosity of glass is 200 poise, T 35000 The temperature at which the viscosity of glass reaches 35,000 poise, T x The upper limit temperature for glass crystallization, T S This refers to the glass softening temperature. The glass's T 200 ≤1600℃; the T of the glass 35000 ≤1089℃; the T of the glass x ≤1000℃; the T of the glass S ≤827℃.
2. The glass as described in claim 1, characterized in that, The glass's T 35000 and the T of the glass x The difference is greater than 80℃.
3. The glass as described in claim 1, characterized in that, When the thickness of the glass is 0.6 mm, the stress intensity CS value of the glass is >900 MPa; And / or, when the thickness of the glass is 0.6 mm, the stress layer depth (DOL) value of the glass is ≥41 μm; And / or, when the thickness of the glass is 0.6 mm, the Vickers hardness value of the glass is >700 HV.
4. A method for preparing the glass according to any one of claims 1 to 3, characterized in that, The method for preparing the glass includes the following steps: S10. Mix, melt, clarify, homogenize, shape, and anneal the components in the raw materials according to the proportions to obtain intermediate glass products; S20. Cut the glass intermediate obtained in step S10. S30. The glass intermediate product after cutting in step S20 is chemically strengthened to obtain the glass.
5. The method for preparing glass according to claim 4, characterized in that, In step S20, the thickness of the glass intermediate product after cutting is controlled to be 0.02mm~0.6mm.
6. The method for preparing glass according to claim 4, characterized in that, In step S30, the chemical strengthening specifically includes the following steps: The glass intermediates after cutting in step S20 are kept at 270℃~320℃ for 25min~40min, and then placed in molten salt for chemical strengthening treatment. The chemical strengthening temperature is controlled at 400℃~430℃ and the chemical strengthening time is controlled at 0.25h~4h. The molten salt comprises 0-1 wt% NaNO3 and 99-100 wt% KNO3.
7. A display device, characterized in that, The display device uses the glass described in any one of claims 1 to 3.
Citation Information
Patent Citations
Alkaline aluminosilicate protective glass capable of realizing ion exchange and preparation method thereof
CN106698928A
Boron aluminum silicate glass and preparation method thereof
CN116102255A
